Comparison between the Linked Color and White Light Imaging Combined Score in the Evaluation of High-Risk Population of Gastric Cancer - Xiu, Jiang Zhang; Bing, Nong; Juan, Ning Jia; Yu, Huang Peng (Turkish Journal of Gastroenterology, 2021)
Background: For patients undergoing gastroscopy, it is necessary to judge whether there is Helicobacter pylori infection, atrophy/intestinalmetaplasia. This study aimed to evaluate and compare the light color imaging (LCI) and white light imaging (WLI) combined scoreduring gastroscopy.Methods: Each included patient underwent normalized gastroscopy with WLI and LCI, and all notable findings were photographed. Fourendoscopists reviewed the endoscopic images of each patient. The clinical information, results of the H. pylori tests were unavailable atreview. The total LCI and WLI scores of each patient were calculated and their detection in high-risk populations of gastric cancer wereevaluated. The diagnostic values of LCI and WLI for intestinal metaplasia were also calculated.Results: In total, 392 patients were included in the study. The degree of inflammation and proportion of active inflammation cases weresignificantly higher in the H. pylori gastritis group than in the non-H. pylori gastritis group; their endoscopic manifestations were alsodifferent. The LCI combined score improved the diagnostic value of each individual observation index in the diagnosis of H. pylori infectioncompared with the WLI combined score. The sensitivity, specificity, and accuracy were 91.9% (91.9% vs 81.5%), 91.1% (91.1% vs80.2%), and 95.8% (95.8% vs 93.2%), respectively. The accuracy of LCI in the diagnosis of intestinal metaplasia was higher than thatof WLI (83.4% vs 69.6%).Conclusion: The LCI and LCI combined score improved the diagnosis of H. pylori gastritis and intestinal metaplasia, and it is consideredvaluable in identifying the high-risk population of gastric cancer.